The checklist of Raphiocarpus species (Gesneriaceae, Didymocarpinae) in the flora of Vietnam with the description of a new species, R. bicallosus - Nguyen, Cuong Huu; Wen, Fang; Pham, Toai Minh; Nguyen, Yen Thi; Bui, Thanh Minh; Bui, Doi The; Nguyen, Khang Sinh; Averyanov, Leonid V. (Phytotaxa, 2023)
The paper presents an annotated checklist of the genus Raphiocarpus (Gesneriaceae) in the flora of Vietnam with a key for identification of all 13 species hitherto recorded in the country, including newly described species. The data for each species include the accepted name, synonyms, citations of relevant regional literature, typification, information on distribution, ecology, and phenology, conservation status, as well as a list of studied specimens and taxonomic notes. Lectotypes for Raphiocarpus asper and R. evrardii are designated. A new species, Raphiocarpus bicallosus, is described here from Xuan Lien Nature Reserve, Thanh Hoa Province, N Vietnam. It is most similar to R. tamdaoensis, but differs in having distinct prophylls, a 3–5-flowered inflorescence, a dark purple-brown corolla limb, the presence of 1 staminode and 2 hairy bosses inside the tube, as well as a glabrous ovary and capsule 5–6 cm long.